A comparison of the various methods used to enhance sprint speed - Behrens, M. J.; Simonson, S. R. (Strength and Conditioning Journal, 2011)
In today's athletics, speed is becoming a more important factor. Speed, stride frequency multiplied by stride length, is the ability to achieve maximum velocity. The purpose of this article is to explore and compare the various methods for enhancing sprint speed. The goal is to provide information to practitioners about the most effective methods for enhancing sprint speed.